Evaluación del nivel de ruido ambiental en el Terminal Terrestre Interprovincial de la ciudad de Tena, cantón Tena, provincia de Napo. - Bravo Armijos, Grey Nathaly (2022)
The level of environmental generated noise at Interprovincial Tena city Bus station was evaluated, starting from environmental baseline construction that includes the compilation of noise reference information through different data collection techniques; Subsequently by established guidelines in applicable standard Ministerial Agreement 097-A, environmental noise was monitored at three periods of higher emission of sound pressure levels, using a class II integrating sound level meter with frequency weighting A, reporting 5 noise samples. 15 seconds for each demonstration point, with a total of seventeen points distributed uniformly and close to affectation critical points using the grid method. Obtained results determined that the highest noise averages are located at external points and corners, having for point P1 (Gabriel Espinosa and Federico Montero streets) an average of 69.2dBA; point P4 (av. 15 de Noviembre and Federico Montero) with 69.8dBA; point P13 (av. 15 de Noviembre and av. del chófer) with 70.2dBA; point P16 (av. del Chófer and calle Gabriel Espinosa) with 69.4dBA, however, all monitored points inside and outside the Terminal are above 60dBA established as permissible limit at environmental standard for commercial use on daytime period. For schematization of noise levels, geographic information program ArcGis was produced, using spatial analysis tools for IDW (inverse distance weighted) interpolation, noise maps were completed for three periods (morning, noon and afternoon) and the overall average. Finally, to counteract socio-environmental problem, a mitigation plan is proposed to control noise in Tena Bus Station, with applied measures to area conditions. It is concluded that noise levels are directly influenced by commercial activities surrounding the area, since it is located in a purely commercial area, added to this, the large vehicular flow that circulates through the main city roads, the av. November 15 and av. del Chófer, they are only two-ways for circulation.